1985
DOI: 10.1515/znb-1985-1226
|View full text |Cite
|
Sign up to set email alerts
|

Mono- and Binuclear Gold(I) Compounds Containing Deprotonated Purines and Pyrimidines

Abstract: Abstract In the presence of alkali and LAuCl one or two -NH - groups of a purine or pyrimidine base can be transformed into - N(AuL)- groups giving stable and soluble compounds containing one or two two-coordinated gold(I) nuclei; mononuclear LAu - Q' or binuclear LAu - Q - AuL with a monodentate Q'- or an exobidentate O-- ligand, resp. (Q'H = adenine, guanine, theobromine, theophylline, azaguanine or cytosine; QH2 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 11 publications
(13 reference statements)
0
8
0
Order By: Relevance
“…323b (c) Alternatively, gold(I) complexes have been obtained by transforming other C-bound ligands. 319,320,324,325 A representative example is the synthesis of bis(imidazolyl)-and bis(thiazolyl)gold complexes 173 by reaction of the lithiated heterocycles 172 with organometallic precursors such as AuCl(THT) and subsequent protonation or alkylation (eq 94). 324,325 Oxidative addition of halogens to these bis(carbene) complexes gives the corresponding gold-(III) derivatives 174 in good yield.…”
Section: V74 Carbene−group 11 Metal Adductsmentioning
confidence: 99%
See 1 more Smart Citation
“…323b (c) Alternatively, gold(I) complexes have been obtained by transforming other C-bound ligands. 319,320,324,325 A representative example is the synthesis of bis(imidazolyl)-and bis(thiazolyl)gold complexes 173 by reaction of the lithiated heterocycles 172 with organometallic precursors such as AuCl(THT) and subsequent protonation or alkylation (eq 94). 324,325 Oxidative addition of halogens to these bis(carbene) complexes gives the corresponding gold-(III) derivatives 174 in good yield.…”
Section: V74 Carbene−group 11 Metal Adductsmentioning
confidence: 99%
“…319,320,324,325 A representative example is the synthesis of bis(imidazolyl)-and bis(thiazolyl)gold complexes 173 by reaction of the lithiated heterocycles 172 with organometallic precursors such as AuCl(THT) and subsequent protonation or alkylation (eq 94). 324,325 Oxidative addition of halogens to these bis(carbene) complexes gives the corresponding gold-(III) derivatives 174 in good yield. 326 (d) Finally, Liu has recently prepared the bis-(imidazolidin-2-ylidene) complex 175 by a carbene- The X-ray diffraction study performed on complex 170b revealed an essentially linear geometry around the metal, the two imidazole rings being twisted 39.7°f rom coplanarity.…”
Section: V74 Carbene−group 11 Metal Adductsmentioning
confidence: 99%
“…[3] In 1989, Burinie tal. have completedt he synthesiso ft he first NHC gold(I) complex [4] but the first studies on the catalytic activity of these complexes were performed more than 10 years later guided by the groups of Herrmann andN olan. [5] By considering the importance of catalysis for basic research, the synthesis and comparison of the catalytic activitieso fd iverse types of NHC gold complexes could significantly contribute to furthera chievementsi nt he field of homogeneous gold catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…However, evidence obtained in XANES experiments (12) suggests that Au(1II) is reduced to Au(1) in vivo (probably by free thiol groups on transport proteins such as albumin) before it enters the cell and becomes available for interaction with DNA. Gold(1) complexes with nucleobases have also been prepared and characterized by Mossbauer, nmr, and infrared spectroscopies (13)(14)(15). Beck et al (16) have determined the structure of the complex of (triphenylphosphine)gold(I) with adenine, where the metal binds to the 'To whom all correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%